Reference framework for metadata description to commensurate data in grain production - Pussi, Katariina; Linna, Petri; Suomi, Pasi; Kaustell, Kim; Pesonen, Liisa (Elsevier, 2025)
Data spaces will bring the need to harmonize the farm collected data for better interoperability. Attention needs also to be paid to data accessibility, since the value of data is strongly linked to its use. The evolving data space technologies will bring service providers that help farmers to translate farm born datasets to data products that can have measurable value. Data products can then be published to the data space catalog, allowing other people to discover and consume them. Data used for data products, decision-making, reporting, or analysis should be reliable and trustworthy. Common metadata standards, catalogs and ontologies will help to achieve this goal. The scope of this paper is to discuss requirements for metadata in grain production.
Keywords: agriculture; smart farming; grain production; data; metadata; data space